SOCIAL FACTS AND RESEARCH FINDINGS ON THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN FORMING STUDENT CHARACTER GLOBALLY - Muhammad Ivansyah; Hasan Baharun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character in the era of globalization, marked by the rapid flow of information and technological developments, which, on the one hand, open wider access to knowledge but, on the other hand, pose a threat to the morality of the younger generation. This study aims to examine the relevance of PAI in strengthening students' faith, morality, and social values by examining social facts, international research findings, academic literature, and theoretical arguments. The research method uses a qualitative approach based on literature studies with content analysis of scientific journals, global institution reports, and Islamic education literature analyzed thematically. The results show that PAI plays a central role in instilling religious, tolerant, and humanistic character through value-based learning, habituation of worship, and teacher role models, with effectiveness greatly influenced by adaptive and contextual implementation strategies. These findings align with Lickona's character education theory and Bandura's social learning theory, and emphasize the urgency of strengthening an innovative, integrative, and multicultural PAI curriculum through collaboration between schools, families, and the community..